IoT Based Air Quality Monitoring System Using LoRaWAN - Sulimat, Mohd Ammiin; Katiran, Norshidah (Evolution in Electrical and Electronic Engineering, 2024)
Insufficient local air quality data hinders control efforts, exacerbating public health and economic concerns amid rising deforestation and urbanization. This project implements an IoT-based air quality monitoring system to track outdoor gas and dust concentrations, fostering public awareness of current pollution levels. The system incorporates an array of sensors, including DHT11, MQ9, MQ135, and a dust sensor, to quantify temperature, humidity, carbon monoxide, carbon dioxide, and PM2.5 levels. A LoRa-enabled microcontroller used to transmit sensor data via a gateway to The Things Network (TTN) platform. TTN seamlessly integrates with ThingSpeak, an IoT server, making the collected environmental data publicly accessible through a web-based ThingSpeak channel and a mobile GUI within the Virtuino application. This design enables users to access real-time data conveniently via a mobile application. The system employs the Malaysian Department of Environment's Air Quality Index (AQI) to categorize pollution severity (good to hazardous). Sensor data from the Air Quality Monitoring system is validated against readings from a Temtop air quality monitoring device, confirming its reliability in measuring CO, CO2, and PM2.5 concentrations.